1999
DOI: 10.1038/sj.bmt.1701907
|View full text |Cite
|
Sign up to set email alerts
|

Expression of C-erbB-2/HER-2 in patients with metastatic breast cancer undergoing high-dose chemotherapy and autologous blood stem cell support

Abstract: Summary:C-erbB-2/HER-2 (designated HER-2) is overexpressed in both primary and metastatic breast cancer and predicts poor prognosis. We investigated the expression of HER-2 in patients with metastatic breast cancer undergoing high-dose chemotherapy (HDCT) with autologous blood stem cell (ABSC) support and correlated the presence (positive) or absence (negative) of HER-2 overexpression in these patients with response to treatment, progression-free survival (PFS) and overall survival (OS). The level of HER-2 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…This analysis showed a significantly shorter PFS and OS for patients with high level of ECD as compared to those with low levels. [18][19] Kim et al 20 reported similar results in assessing HER2 status by IHC. In contrast to our and the previously quoted studies, comparing ECD and HER2 status evaluated by IHC and FISH on primary tumors in patients treated with HD alkylating agents after anthracycline-based induction chemotherapy, Harris et al 22 concluded that ECD only can identify a subset of patients at worse prognosis, while IHC and FISH were not correlated with outcome.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This analysis showed a significantly shorter PFS and OS for patients with high level of ECD as compared to those with low levels. [18][19] Kim et al 20 reported similar results in assessing HER2 status by IHC. In contrast to our and the previously quoted studies, comparing ECD and HER2 status evaluated by IHC and FISH on primary tumors in patients treated with HD alkylating agents after anthracycline-based induction chemotherapy, Harris et al 22 concluded that ECD only can identify a subset of patients at worse prognosis, while IHC and FISH were not correlated with outcome.…”
Section: Discussionsupporting
confidence: 65%
“…The majority of these studies showed a worse outcome for HER2-positive patients. [18][19][20][21][22] Overall, these studies included 274 patients with HER2 assessed on the tumor, and the patients were treated with a variety of induction regimens, not including taxanes.…”
Section: Metastatic Breast Cancermentioning
confidence: 99%
“…Further, recent data suggest that the level of HER-2 expression may not only be a prognostic factor, but may also predict response to different treatments. [6][7][8]16,17 The prognosis of patients with metastatic breast cancer is very poor with less than 5% surviving 10 years after detection of metastasis. 18 As a result, the main objective of treatments Progression-free survival Figure 1 Kaplan-Meier estimates of overall survival (OS) and progression-free survival (PFS) of patients with metastatic breast cancer (n = 46) following HDCT and ABSCT.…”
Section: Discussionmentioning
confidence: 99%
“…These results support our earlier findings on the prognostic power of HER-2 in the HDCT treatment of patients with metastatic breast cancer. 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation